Competing acetate consumption and production inside a microbial electrolysis cell. Issue 4 (August 2020) - Hasibar, Benedikt; Ergal, İpek; Abreu Dias, Sonia; Bochmann, Günther; Rittmann, Simon K.-M. R.; Fuchs, Werner
Graphical abstract: Highlights: Consumption of H2 by homoacetogens outweighs formation of new H2 . High H2 partial pressure reduces acetate consumption in MECs. Homoacetogenesis leads to a decrease in H2 yield. N2 purging is a promising option to avoid homoacetogenesis. Deltaproteobacteria most abundant class in acetate fed MECs. Abstract: During dark fermentative biological hydrogen (H2 ) production acetate is the main metabolic end product. The subsequent anaerobic conversion of acetate to H2 is thermodynamically not favorable. In microbial electrolysis cells (MECs), these thermodynamic limits can be overcome by electroactive bacteria, using the anode as electron acceptor. In mixed culture MECs homoacetogenic bacteria can cause an unwanted decrease in H2 yield as they consume the produced H2 for acetate production, thus reversing the desired reaction. This study reveals the influence of H2 partial pressure on MEC processes and shows how to inhibit homoacetogenesis. Single chamber MECs were inoculated with mixed cultures and fed with acetate at a voltage of 0.8 V. One set was purged with a mixture of H2 and CO2, the other one with nitrogen (N2 ) in order to adjust the H2 partial pressure. An increase in acetate concentration was observed in MECs with high H2 partial pressure. N2 sparging inhibited homoacetogenic activity and facilitated microbial electrolysis. DNA sequencing results show that the most abundant classes were Deltaproteobacteria and Clostridia in MECs purged with N2 and H2 /CO2, respectively. The results reveal the dual influence of the H2 partial pressure during MEC operation and provide new insights regarding the construction and operation of bioelectrochemical systems.